Developing RME-Based Learning Trajectory for Teaching Addition to A Dyscalculia Student in Elementary School - Ahmad Fauzan; Cahyo Dwi Andita; Gusti Rada; Afifah Zafirah; Abdul Halim bin Abdullah (Didaktik Matematika, 2022)
This research aimed to design an RME-based learning trajectory for a dyscalculia student to learn the addition of whole numbers. The research used design research approach that consists of three phases: preparing for the experiment, conducting the experiment, and retrospective analysis. This research's data collection techniques were observations, interviews, videotaping, and analyzing the student works. The main result of this research is the learning trajectory for teaching addition of whole numbers to a dyscalculia student using RME approach. The series of activities in the learning trajectory are addition of whole numbers between 1 and 10 by combining the objects, addition of whole numbers between 1 and 10 using number relations, addition of whole numbers between 1 and 20 using number relations, and finding the concept of place value of tens and ones in addition of numbers. This research also shows the cognitive improvement of dyscalculia student in learning the addition of whole numbers. Learning activities carried out by the dyscalculia student help him to shif from informal knowledge to formal mathematical knowledge in order to understand the concept of addition of whole numbers. It makes dyscalculia student has number sense, number construction, and number relation abilities which increase significantly in the learning process.